2019
DOI: 10.1038/s41598-019-46264-y
|View full text |Cite
|
Sign up to set email alerts
|

Repair Effects of Astragalus Polysaccharides with Different Molecular Weights on Oxidatively Damaged HK-2 Cells

Abstract: This study investigated the repair effects of three Astragalus polysaccharides (APSs) with different molecular weights (Mws) on injured human renal proximal tubular epithelial (HK-2) cells to reveal the effect of Mw of polysaccharide on cell repair. A damage model was established by injuring HK-2 cells with 2.6 mM oxalate, and APS0, APS1, and APS2 with Mw of 11.03, 4.72, and 2.61 KDa were used to repair the damaged cells. After repair by APSs, the morphology of damaged HK-2 cells gradually returned to normal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 44 publications
(49 reference statements)
1
27
0
Order By: Relevance
“…reduced 76% of risk compared to 51% for the other CHM. Studies reported that Astragalus mongholicus Bunge reduced inflammation and prevented renal interstitial fibrosis ( Wang et al, 2015b ; Shan et al, 2016 ; Zhou et al, 2017 ), regulated cell apoptosis and cell cycle arrest ( Tay et al, 2019 ) and last but not least, it promoted repair function by activating the Nrf2-Keap1 signaling pathway and inhibiting inflammation ( Han et al, 2019 ). The third cluster with core CHM of Rheum palmatum L (or Rheum tanguticum (Maxim.…”
Section: Discussionmentioning
confidence: 99%
“…reduced 76% of risk compared to 51% for the other CHM. Studies reported that Astragalus mongholicus Bunge reduced inflammation and prevented renal interstitial fibrosis ( Wang et al, 2015b ; Shan et al, 2016 ; Zhou et al, 2017 ), regulated cell apoptosis and cell cycle arrest ( Tay et al, 2019 ) and last but not least, it promoted repair function by activating the Nrf2-Keap1 signaling pathway and inhibiting inflammation ( Han et al, 2019 ). The third cluster with core CHM of Rheum palmatum L (or Rheum tanguticum (Maxim.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the damaged renal epithelial cells are repaired [5] or the cells are preprotected [6], the probability of kidney stone formation can be greatly reduced. Exogenous plant polysaccharides with antioxidant function can effectively preprotect cells [7] and improve the ability of cells to resist oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…Natural CSPs have difficulty crossing cell membrane and entering cells to play a role because of their large molecular weight [5,17,18]. Degradation of CSPs with large molecular weight can better exert their biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the complex chemical structure of APSs, their various biological activities, including immunomodulatory, anti-inflammatory, antioxidant, anti-tumor, and hypoglycemic, have also received extensive attention ( Wang et al, 2018 ; Han et al, 2019 ; Zheng et al, 2020 ), as shown in Table 2 . APSs play an immunoregulatory role in many aspects.…”
Section: Introductionmentioning
confidence: 99%